Non-invasive assessment of progesterone and cortisol levels in relation to reproductive and stress behaviours of rusa unicolor kerr in captivity - Abdul Hamid, Noor Haida (2022)
Sambar Deer, Rusa unicolor (KERR, 1792) are listed as ‘vulnerable’ in the IUCN Red List. In Malaysia, they are bred in semi-captive and captive environment under governmental management, but this has produced a variety of results. For example, breeding in zoos led to sambar deer becoming accustomed to human presence, whereas the current reintroduction programme by semi-captive centres was ineffective because sambar deer still face a high risk of extinction in the wild. This study aimed to assess sambar deer reproductive and stress behaviours and its progesterone and cortisol profiles in captivity while establish an ethogram on reproductive and stress behaviours. Also, to study the relationship between reproductive and stress behaviours with environmental parameters and correlate reproductive and stress behaviours of semi-captive sambar deer with progesterone and cortisol. In captive study, the frequency of each behaviour performed by 6 female sambar deers was calculated by session (morning, afternoon, evening) in the form of percentage. The reproductive and stress hormones in faecal samples were analysed using ELISA. Meanwhile, in semi-captive study, data on 8 female sambar deers were collected to assess their reproductive and stress behaviours. A Generalized Linear Model (GLM) was used to analyse each behaviour with the environmental parameters. Data for behavioural-hormonal correlation study were collected from 3 female sambar deers. Daily data on total frequency of each behaviours were correlate with concentration of progesterone and cortisol metabolites using Pearson Correlation Test. Study in captivity environment showed more reproductive behaviours in the morning and evening session. Sambar deer were suggested to be on anoestrus due to average reading of - 25.9 ng/g progesterone metabolites concentration. It could be suggested that, they were not in stress due to low cortisol metabolites concentration of - 0.3 ng/g. Study on semicaptivity environment showed more reproductive behaviours in the morning when there was no rain, the temperature was 28°C and without the presence of workers. When there was no rain and an average temperature of 29°C, stress behaviours were more prevalent. Negative correlation between reproductive behaviours and progesterone levels was observed at the early, middle, and at the end of the month. The occurrence of oestrus among sambar deers in semicaptivity may last for 24 hours and had a shorter oestrus cycle (13 days). A behavioural-hormonal prediction model was constructed to help in predicting future reproductive event in captivity. The low level of positive correlation between stress behaviours and cortisol metabolite concentrations (r = 0.32) suggests that sambar deers living in a semi-captive environment are not under stress. Further study on other reproductive hormones to correlate with its behaviours needs to be conducted as it is very important to understand what these species are, and how they are currently managed in the wild and in captivity.